Tradisi Tilik pada Masyarakat Jawa dalam Sorotan Living Hadis (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Not all of Javaneses traditions are rejected by Islam, one of them is the practice of tilik. This tradition in the community has been accommodated by Islam and categorized as a term of friendship. The tradition of tilik will be discussed by using the perspective of living hadith. The theory applied in the social study of Peter L. Berger and Thomas Luckmann, by using narrative and structural analysis the following questions are explained. Firstly, how to integrate tilik tradition in Javanese society link to and the Prophet's Hadith. Second, what are the true values that exist in this tradition so that it is still being practiced until today? This paper concludes that the tilik tradition has been a ṣaḥīḥ history. The Javanese people whose culture of harmony and gathering among factors that strengthen the implementation of this ritual.
Keywords: Tilik; Tradisi Jawa; Living Hadis